THE ROLE OF TRADE UNIONS IN INCREASING SOCIAL AND POLITICAL ACTIVITY OF YOUNG GENERATION - Bakhromjon Akhmadjonov (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the role of trade unions in increasing the social and political activity of young people in the conditions of modernizing Uzbekistan.